PENGARUH TOTAL ASSET TURNOVER (TATO), RETURN ON ASSET (ROA) DAN DEBT TO ASSET RATIO (DAR) TERHADAP PERTUMBUHAN LABA PADA PT. ADHI KARYA (PERSERO) TBK - M. Rizki Andriansyah; Aliah Pratiwi; Nurhayati (Universitas Mahendradatta, 2025)
This research aims to determine the effect of Total Asset Turnover, Return On Assetsand Debt to Asset Ratio on profit growth. At PT. Adhi Karya Persero Tbk. The instrument for thisresearch is to use financial reports between the balance sheet and profit and loss reports at PT.Adhi Karya Persero Tbk. The data used in this research instrument is data on net profit, totalsales, total debt and total assets from 2013-2022. Meanwhile, the sampling technique used waspurposive sampling. The criteria are based on the availability of up-to-date data and researchvariable data used. The data in this research was processed using SPSS. The hypothesis testingmethod uses a significance level of 5%. The research results show that Total Asset Turnover(TATO) has no significant effect on profit growth, Return on Assets (ROA) has no significant effecton profit growth and Debt to Asset Ratio (DAR) has no significant effect on profit growth. And simultaneously Total Asset Turnover (TATO), Return On Assets (ROA) and Debt to Asset Ratio(DAR) have no effect on profit growth at PT. Adhi Karya Tbk